Studi Kelayakan Pengembangan Repositori Institusi Pada Institut Teknologi Del - Tiurma Lumban Gaol; Irman Hermadi; Imas Sukaesih Sitanggang (Jurnal Pustakawan Indonesia, 2016)
Institutional repository is an essential part functioning as a storage for keeping the collection of publication digitally. Del Institute of Technology (ITD) has its own collection of institutional publication but it does not have institutional repository. Before developing the application, it is essential that a feasibility study be conducted in order to ensure the development of ITD's application will run well. Feasibility study is conducted through first phase of knowledge management system life cycle and the model is IPB institutional repository. Based on the analysis of the feasibility of the ITD infrastructure percentages obtained in building institutional repository is 51.96%. The percentage is derived from the percentage of the value of the following eligibility is infrastructure (21.44%), human resources (14.33%), Budget (0%), Rules / SOP / SK (3,40%) and Content (12.79%). Based on the results of the study referred to the several things that need to be addressed in the effort to develop the institutional repository ITD and refer to the model repository development in IPB is to provide the infrastructure that is software as a tool for transferring media content repository, making decree team, create a SOP for digital documents and the handover of the scientific work of the academic community ITD. Keywords: Feasibility Study, Institutional Repository, Knowledge Management Systems